2015
DOI: 10.1111/jfs.12184
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of Nutmeg Oil in Pork and Its Possible Mechanism

Abstract: The aim of this study is to investigate the antibacterial characteristics and mechanisms of nutmeg oil. In this paper, 54 chemical compositions of nutmeg oil were analyzed by gas chromatography–mass spectrometry (GC–MS). The major volatile components of nutmeg oil were sabinene (39.12%) and alpha‐pinene (11.96%). In addition, nutmeg oil showed significant antibacterial activity, minimum inhibitory concentration, and minimum bactericide concentration of seven pathogens are 0.05 and 0.1%, respectively, and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
3
8
0
2
Order By: Relevance
“…These results were consistent with the earlier findings (Cui et al 2015), indicating that the nutmeg oil in pork could destroy the cell wall and cell membrane of E. coli and S. aureus. The leakage of ALP-ase could degrade the main nucleic acid components, such as RNA and DNA.…”
Section: Antimicrobial Activity Of Black Pepper Organic Extractsupporting
confidence: 93%
“…These results were consistent with the earlier findings (Cui et al 2015), indicating that the nutmeg oil in pork could destroy the cell wall and cell membrane of E. coli and S. aureus. The leakage of ALP-ase could degrade the main nucleic acid components, such as RNA and DNA.…”
Section: Antimicrobial Activity Of Black Pepper Organic Extractsupporting
confidence: 93%
“…The essential oil EO2 investigated in this study has a similar composition, meaning it could also be efficient against these pathogens at higher concentrations. In another study, the nutmeg essential oil with similar quantity of volatile compounds had a significant effect on the inhibition of the growth of E. coli and S. aureus [34]. In this study, we found that essential oil EA2 (0.5%) inhibited E. faecalis.…”
Section: Discussionsupporting
confidence: 54%
“…dari suku Myristicaceae, yang dikenal sebagai Pala di Indonesia telah digunakan secara tradisional untuk rempah-rempah dan obat-obatan untuk meningkatkan sistim imun dan radioprotektif 1 , antidiabetes 2 , antikonvulsan, antimoluska 3 ,hepatoprotektif 4 , antikarsinogen 5 , aprodisiak 6 , antidepresan 7 , antioksidan 8,9 , antimikroba. 10,11,12 Konstituen utama Pala (M. fragrans Houtt) telah ditemukan sebagai turunan alkil benzena (miristisin, elemisin, safrol dll. ), Terpen, α-pinene, β-pinene, asam myristat dan trimiristin.…”
Section: Pendahuluanunclassified